High-air-permeability imitated green leaf material and preparation method thereof
Polyacrylonitrile nanofiber nonwoven fabric was prepared in one step by electrospinning technology, which solved the problems of cumbersome processing and poor air permeability of existing green leaf-like hyperspectral camouflage materials. It achieved a green leaf-like material with high air permeability and similar spectral characteristics, which is suitable for outdoor tents and individual soldier equipment.
Patent Information
- Application Number
- CN202511610365.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-05
- Publication Date
- 2026-01-16
AI Technical Summary
Existing green leaf-like hyperspectral camouflage materials have complicated coating and finishing processes and poor breathability and comfort, making it difficult to meet the high breathability and comfort requirements of outdoor tents and individual soldier equipment.
Polyacrylonitrile nanofiber nonwoven fabric is prepared in one step using electrospinning technology. Cationic dyes, hygroscopic salts and polyacrylonitrile are added to a solvent, stirred and then electrospinned to form a highly breathable green leaf-like material. The material does not require coating or dyeing finishing.
It achieves high breathability and spectral characteristics similar to natural green leaves, simplifies the processing, and is suitable for high-spectral camouflage textiles in fields such as outdoor tents and individual soldier clothing, meeting the requirements for breathability and comfort.
Smart Images

Figure CN121344870A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to a high air permeability green leaf imitating material and a preparation method thereof, and belongs to the field of hyperspectral camouflage. BACKGROUND
[0002] Hyperspectral detection technology is a ground object detection reconnaissance technology that has developed rapidly in recent years, with wide-band spectrum from visible light (380-780 nm) to near-infrared (780-2500 nm) and high-precision (spectral resolution better than 10 nm) recognition capability.
[0003] Green leaves are one of the most common background environments, and thus become the main imitating object of hyperspectral camouflage materials. Green leaves have the following typical spectral characteristics: (1) a "green peak" of about 8%-20% reflectance appears near 550 nm, which is related to chlorophyll content; (2) the reflectance sharply rises in the range of 680-780 nm, forming a "red edge"; (3) the reflectance is relatively high in the range of 780-1300 nm, reaching 40%-60%, forming a "near-infrared plateau", which is mainly caused by the scattering of internal pore structure and pigment particles in the leaf; (4) there are "water absorption valleys" near 1450 nm and 1930 nm, with reflectances of 10%-30% and 3%-10% respectively, which are mainly caused by the absorption of water in the leaf.
[0004] At present, the developed hyperspectral camouflage materials imitating green leaves mainly include: (1) a hydrogel-based hyperspectral camouflage fabric, which is first subjected to screen printing treatment by using a printing paste containing a colorant, and then is impregnated with a prepolymer solution to obtain a high-hygroscopic hydrogel composite fabric by copolymerization, such as the technical solution disclosed in Chinese Invention Patent CN119529317A; (2) a hygroscopic metal salt-based hyperspectral camouflage coating, which is prepared by using an organic high-molecular varnish as a base material and an inorganic pigment and a hygroscopic salt aqueous solution as a coating material to form a bottom coating layer with a certain thickness (0.5-1.5 mm), and then coating a layer of 0.05-0.25 mm varnish to obtain a hyperspectral camouflage coating, such as the technical solution disclosed in Chinese Invention Patent CN118222138A; (3) an inorganic silicate-based hyperspectral camouflage coating, which mainly includes a water-containing inorganic silicate binder, chromium oxide green pigment and sodium polyphosphate modified additive, and the inorganic coating has good water retention and ultraviolet resistance, such as the technical solution disclosed in Chinese Invention Patent CN115820007A.
[0005] Although the above-mentioned materials have similar spectral curves to vegetation, they all rely on post-coating finishing methods, which have the disadvantages of complicated processing steps and high use cost; and the obtained coating material structure is dense, which greatly damages the original porous and air permeable properties of the textile, and cannot meet the performance requirements of high air permeability and comfort for field tents and individual equipment. SUMMARY
[0006] In order to solve the problems of complicated finishing process, poor air permeability and comfort, and difficulty in application in the field of camouflage tents and individual equipment in the existing green leaf imitating high spectrum camouflage material, the application provides a high air permeability green leaf imitating material and a preparation method thereof, and finally a polyacrylonitrile nanofiber nonwoven fabric with high air permeability, high spectrum camouflage function and high air permeability and comfort is obtained without any coating or printing and finishing.
[0007] In order to achieve the above-mentioned purpose, the application adopts the following technical scheme: The first object of the application is to provide a preparation method of a high air permeability green leaf imitating material, which comprises the following steps: (1) adding cationic dyes, hygroscopic salt and polyacrylonitrile into a solvent, stirring at room temperature to obtain a spinning solution; (2) electrospinning the spinning solution obtained in step (1) to obtain the high air permeability green leaf imitating material; In the spinning parameters, the voltage is 10-50kV, the spinning distance is 5-10cm, the liquid supply speed is 0.5-10mL / h, the spinning environment temperature is 10-40℃, and the spinning environment humidity is 5-30%.
[0008] In one embodiment, the cationic dyes in step (1) are composed of cationic red X-RGL, cationic yellow X-8GL and cationic blue X-GRRL.
[0009] In one embodiment, the mass ratio of cationic red in the cationic dyes is 33wt%, the mass ratio of cationic yellow is 28wt%, and the mass ratio of cationic blue is 39wt% in the dye system.
[0010] In one embodiment, the mass ratio of the cationic dyes to the solvent in step (1) is 0.3-1.5wt%, preferably 0.6-1.2wt%, and further preferably 0.9-1.2wt%.
[0011] In one embodiment, the solvent in step (1) is one or more of N,N-dimethylformamide, N,N-dimethylacetamide and dimethyl sulfoxide.
[0012] In one embodiment, the hygroscopic salt in step (1) is one or more of lithium chloride, calcium chloride, silica gel, montmorillonite and molecular sieve.
[0013] In one embodiment, the mass ratio of the hygroscopic salt to the solvent in step (1) is 5-15wt%, preferably 8-12wt%, and further preferably 10wt%.
[0014] In one embodiment, the stirring speed in step (1) is 200-1000 rpm.
[0015] In one embodiment, the polyacrylonitrile in step (1) accounts for 6-18 wt% of the solution.
[0016] In one embodiment, the spinning distance in step (2) is 6-10 cm.
[0017] In one embodiment, the humidity in the spinning environment in step (2) is 10-30%.
[0018] A second object of the present application is to provide a high-air-permeability artificial green leaf material obtained by the above method.
[0019] In one embodiment, the high-air-permeability artificial green leaf material has a spectral correlation coefficient of 0.916-0.952 with natural green leaves and an air permeability of 17.9-20.1 mm s -1 .
[0020] A third object of the present application is to provide a use of the high-air-permeability artificial green leaf material in the field of high-spectral camouflage textiles such as field tents and individual clothing.
[0021] Advantages: (1) The preparation method of the polyacrylonitrile nanofiber high-spectral camouflage material is simple, does not require any coating, dyeing, and finishing, and has the advantages of short processing flow and easy mass production. (2) The high-air-permeability artificial green leaf material has similar reflection spectrum characteristics to natural green leaves and also maintains a large number of pore channels, which is conducive to improving the air permeability and comfort of camouflage equipment and is expected to meet the urgent demand for air-permeability and comfort high-spectral camouflage textiles in the field of field tents and individual clothing. BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 Figure 1 is a SEM image of the surface morphology of the high-air-permeability artificial green leaf material of Example 1 of the present application. Figure 2 Figure 2 is a reflection spectrum curve of the fiber material prepared in Example 1 and Comparative Example 1 of the present application and natural green leaves. Figure 3 Figure 3 is a graph of the air permeability and spectral correlation coefficient of the fiber material prepared in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present application, instead of all the embodiments. Based on the embodiments in the present application, all the other embodiments obtained by a person of ordinary skill in the art without creative effort belong to the scope of protection of the present application. The following specific embodiments further describe the present application.
[0024] The test method involved in the present application is as follows: (1) Micro-morphology structure characterization The micro-morphology structure of the obtained sample was characterized and tested by a scanning electron microscope (Hitachi SU8100).
[0025] (2) Spectral correlation coefficient test The reflectance spectrum curve of the sample was measured by an ultraviolet-visible-near infrared spectrophotometer (Lambda 950), and the spectral correlation coefficient of the sample and the natural green leaf was calculated according to the Pearson correlation coefficient formula.
[0026] (3) Air permeability test The air permeability of the sample was tested by a full-automatic air permeability tester (YG461G) according to GB / T5453-1997 "Determination of air permeability of textiles".
[0027] The raw material sources involved in the present application are as follows: Cationic dyes (containing three kinds: cationic red X-RGL, cationic yellow X-8GL and cationic blue X-GRRL) were purchased from Zhejiang Longsheng Group Co., Ltd.; polyacrylonitrile (weight average molecular weight 85000), lithium chloride (≥99.9%) and N,N-dimethylformamide (≥99.5%) were purchased from Sinopharm Chemical Reagent Co., Ltd.
[0028] Embodiment 1 A preparation method of a high-air-permeability green-leaf-imitating material, comprising the following steps: (1) Preparation of spinning solution 0.9 g of cationic dyes (in which cationic red accounts for 33 wt% of the mass ratio of the dye system, cationic yellow accounts for 28 wt% of the mass ratio of the dye system, and cationic blue accounts for 39 wt% of the mass ratio of the dye system), 10 g of lithium chloride and 10 g of polyacrylonitrile were added to N,N-dimethylformamide solvent, and stirred at a speed of 600 rpm at room temperature for 12 h to prepare 100 g of spinning solution; (2) Preparation of high-air-permeability green-leaf-imitating material The above spinning solution was transferred to an electrospinning device for electrospinning. The spinning parameters were adjusted as follows: voltage 30kV, distance 8cm, liquid supply speed 2mL / h, ambient temperature 30℃, and ambient humidity 20%. This yielded a highly breathable green leaf-like material, namely a highly breathable green leaf-like nanofiber nonwoven fabric.
[0029] The microstructure of the sample obtained in this embodiment is as follows: Figure 1 As shown, the material has a spectral correlation coefficient of 0.984 with natural leaves and an air permeability of 19.2 mm / s.
[0030] Example 2 The only difference from Example 1 is that the cationic dye content in the spinning solution in step (1) is 0.6g and 1.2g, respectively, while other formulation parameters (such as the mass ratio of each component) and spinning process conditions are the same as in Example 1.
[0031] The properties of the highly breathable, leaf-like material obtained in this embodiment are shown in the table below: Table 1. Performance of highly breathable leaf-like materials
[0032] Example 3 The only difference from Example 1 is that the lithium chloride content in the spinning solution in step (1) is 6g, 8g, and 12g, respectively, while other formulation parameters (such as the mass ratio of each component) and spinning process conditions are the same as in Example 1.
[0033] The performance of the highly breathable green leaf-like sample obtained in this embodiment is shown in the table below: Table 2. Performance of highly breathable leaf-like materials
[0034] Example 4 The only difference from Example 1 is that the spinning distance in step (2) of electrospinning is 6cm and 10cm respectively, while other formulation parameters (such as the mass ratio of each component) and spinning process conditions are the same as in Example 1.
[0035] The performance of the highly breathable green leaf-like sample obtained in this embodiment is shown in the table below: Table 3. Performance of highly breathable leaf-like materials
[0036] Example 5 The only difference from Example 1 is that the ambient humidity during the electrospinning process in step (2) is 10% and 30%, respectively. Other formulation parameters (such as the mass ratio of each component) and spinning process conditions are the same as in Example 1.
[0037] The performance of the highly breathable green leaf-like sample obtained in this embodiment is shown in the table below: Table 4. Performance of highly breathable leaf-like materials
[0038] Comparative Example 1 The only difference from Example 1 is that the amount of lithium chloride added in step (1) is 0.8g, and the other parameters and conditions are the same as in Example 1.
[0039] Comparative Example 2 The only difference from Example 1 is that the amount of lithium chloride added in step (1) is 1.6g, and the other parameters and conditions are the same as in Example 1.
[0040] Comparative Example 3 The only difference from Example 1 is that the amount of cationic dye added in step (1) is 0.1g, and all other parameters and conditions are the same as in Example 1.
[0041] Comparative Example 4 The only difference from Example 1 is that the amount of cationic dye added in step (1) is 18g, and the other parameters and conditions are the same as in Example 1.
[0042] Comparative Example 5 The only difference from Example 1 is that the amount of polyacrylonitrile added in step (1) is 4g, and the other parameters and conditions are the same as in Example 1.
[0043] Comparative Example 6 The only difference from Example 1 is that the amount of polyacrylonitrile added in step (1) is 20g, and the other parameters and conditions are the same as in Example 1.
[0044] Comparative Example 7 The only difference from Example 1 is that the spinning distance in step (2) of the electrospinning process is 20cm, while other formulation parameters (such as the mass ratio of each component) and spinning process conditions are the same as in Example 1.
[0045] The nanofibers obtained in this comparative example were cured for a sufficient and long time. The nanofibers exhibited obvious filament drifting, resulting in poor structural stability and easy loosening of the nonwoven fabric, making it unusable.
[0046] Comparative Example 8 The only difference from Example 1 is that the ambient humidity during the electrospinning process in step (2) is increased to 50%, while other formulation parameters (such as the mass ratio of each component) and spinning process conditions are the same as in Example 1.
[0047] The spinning jet obtained in this comparative example undergoes rapid phase separation with ambient moisture molecules, which easily clogs the spinneret, results in poor spinnability, significant nanofiber solidification and lint accumulation, and leads to poor structural stability and loosening of the nonwoven fabric, making it unusable.
[0048] Effect Analysis Figure 1 This is a microscopic morphology diagram of the green leaf-inspired spectral simulation fiber material of Embodiment 1 of the present invention. The abundant pore structure between the fibers can rapidly transport air molecules.
[0049] Figure 2 The figure shows the reflectance spectral curves of the fiber materials prepared in Example 1 and Comparative Example 1 and natural green leaves. The figure shows that the reflectance curves of the sample obtained in the example and natural green leaves in the full spectrum of 400~2500nm are basically the same, while the reflectance of the comparative example and natural green leaves in the 1000~2500nm band are very different.
[0050] Table 5 shows the spectral simulation and air permeability test results of the fiber materials prepared in Example 1 and different comparative examples of the present invention. The three fiber materials prepared in the examples of the present invention have high spectral correlation coefficients (0.984) and air permeability (19.2 mm / s), which is due to the beneficial effect of the combination of fiber material colorant and water-absorbing agent with porous structure. However, Comparative Example 1 has a low spectral correlation coefficient (0.774) because of its low lithium chloride content, which leads to poor simulation of the water absorption valley characteristics of green leaves in the near-infrared band. Comparative Example 2 has an excessive salt content in the spinning solution, which makes the jet unstable and easily causes the spinneret to be blocked, resulting in poor spinnability and uneven fibers. Comparative Example 3 has a low dye content, which leads to poor simulation of the green peak and red edge characteristics of natural green leaves in the visible light band, resulting in a low spectral correlation coefficient (0.615). Comparative Example 4, due to its excessive dye content, resulted in an overly dark color with a significant difference in spectrum from natural leaves, and its spectral correlation coefficient remained low (0.703). Comparative Example 5, due to its insufficient polyacrylonitrile content in the spinning solution, resulted in numerous beads / granules, uneven fibers, and easy material breakage, rendering it unusable. Comparative Example 6, due to its excessive polyacrylonitrile content in the spinning solution, resulted in excessively high viscosity and unstable jetting, easily causing nozzle clogging, leading to poor spinnability and uneven fibers. Comparative Example 7, due to its large spinning distance, resulted in poor spinnability, easy fiber scattering and lint accumulation during spinning, and poor structural stability and looseness of the resulting material, rendering it unusable. Comparative Example 8, due to its high humidity in the spinning environment, resulted in rapid phase separation of the spinning solution, easy clogging of the spinneret, poor spinnability, obvious fiber solidification and lint accumulation, poor structural stability and looseness of the material, rendering it unusable.
[0051] Table 5. Performance of Example 1 and different comparative samples of the present invention
[0052] In summary, the polyacrylonitrile nanofiber nonwoven fabric prepared by this invention exhibits spectral characteristics similar to natural green leaves and possesses excellent breathability. Furthermore, the preparation method of this material is simple and requires no coating or finishing process, meeting the high breathability and comfort requirements of hyperspectral camouflage materials in fields such as outdoor tents and individual soldier clothing.
[0053] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.
Claims
1. A method for preparing a high air permeability green leaf-imitating material, characterized by, The method comprises the following steps: (1) adding cationic dyes, hygroscopic salt and polyacrylonitrile into a solvent, stirring at normal temperature to obtain a spinning solution; the cationic dyes are composed of cationic red X-RGL, cationic yellow X-8GL and cationic blue X-GRRL; (2) electrospinning the spinning solution obtained in step (1) to obtain the product; wherein the spinning parameters are as follows: voltage is 10-50 kV, spinning distance is 5-10 cm, liquid supply speed is 0.5-10 mL / h, spinning environment temperature is 10-40℃, and spinning environment humidity is 5-30%.
2. The method of claim 1, wherein, The mass ratio of the cationic dyes to the solvent in step (1) is 0.3-1.5 wt%.
3. The method of claim 1, wherein, The hygroscopic salt in step (1) is one or more of lithium chloride, calcium chloride, silica gel, montmorillonite and molecular sieve.
4. The method of claim 1, wherein, The mass ratio of the hygroscopic salt to the solvent in step (1) is 5-15 wt%.
5. The method of claim 1, wherein, The mass ratio of the polyacrylonitrile to the solution in step (1) is 6-18 wt%.
6. The method of claim 1, wherein, The spinning distance in step (2) is 6-10 cm.
7. The method of claim 1, wherein, The spinning environment humidity in step (2) is 10-30%.
8. The high-air-permeability artificial green leaf material obtained by the method according to any one of claims 1-7.
9. The high permeability green leaf-imitating material according to claim 8, characterized by The high-air-permeability green-leaf-imitating material has a spectrum correlation coefficient of 0.916-0.952 with natural green leaves, an air permeability of 17.9-20.1 mm s -1 .
10. The application of the high-air-permeability artificial green leaf material according to any one of claims 8 or 9 in the field of high-spectrum camouflage textiles such as field tents and individual clothing.
Citation Information
Patent Citations
Hyperspectral stealth coating and preparation method thereof
CN115820007A
Preparation method of hyperspectral camouflage coating
CN118222138A
Plant leaf imitating hydrogel composite material and preparation method thereof
CN119529317A
